Pengaruh Pendekatan Pembelajaran Technological Pedagogical Content Knowledge (TPACK) Terhadap Hasil Belajar Siswa - Sutrisno; Isnaini, Muhammad; Sukirman; Alimron; Aisah, Siti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This thesis discusses the influence of the TPACK learning approach on student learning outcomes in PAI subjects for class X students at SMA Negeri 22 Palembang. The aim of this research is to find out how much influence the TPACK learning approach has on student learning outcomes in PAI subjects. The method used in this research is a quantitative method with a quasi-experimental type of research. The sample in this study was 89 students, namely 45 control class students and 44 experimental class students taken using the purposive sampling technique from a population of 627 students. Data collection techniques use interview, test and documentation methods. In the control class, the average pretest score was 49.533 and the posttest was 53.4. Meanwhile, in the experimental class, the average pretest score was 53.204 and posttest was 81.836. So from this average value it can be concluded that implementing the TPACK learning approach can increase the average value of student learning outcomes in PAI subjects. Hypothesis testing was carried out using the T-Test with a sig value. (2-tailed) is 0.000 < 0.05 so it can be concluded that there is a significant influence of the TPACK Learning Approach on Student Learning Outcomes in PAI Subjects for Class X Students at SMA Negeri 22 Palembang.